Cover Image, Volume 56, Issue 21. Issue 21 (1st November 2018) - Unknown
Abstract : In their paper on page 1433, Natalia Bourguignon and colleagues report a novel accessible and cost‐effective method to fabricate polydimethylsiloxane (PDMS) microdevices. The team uses flexible molds (Fmold) with high‐dimensions (up to 2 meters), high‐resolution structures (up to 25 µm), variable heights (from 50 up to 1500 µm), long durability, low cost, and direct design from CAD software that is available worldwide. (DOI:10.1002/polb.24726 )